Teaching concept of Brevity Using Interactive Whiteboard in an ESL CLassroom - Bano, Nikhat (Voices of Teachers and Teacher Educators, 2023)
This paper is about teaching the shortening of long and elaborate passages through precis writing and summary writing, to senior secondary students using an Interactive White Board. Learning the shortening of passages is one of the most important advanced writing skills to learn in the present era. In an era, which is marked by technological advancements in almost all fields, including education. Technology in education has played a major role in making teaching-learning accessible, interesting and easy to understand. It has become convenient for teachers to explain a concept using multiple examples which enhances learning and retention. Today one is surrounded by knowledge and information, in such conditions senior secondary-level students must know what to look for and what to let go. They must know the skills of searching, skimming scanning and processing this information using their cognition, saving it and using it when needed. All these skills become easier to teach and learn in a large classroom when it is facilitated with ICT tools (Information and Communication Tools) In this, the author has shown the utility of an Interactive whiteboard (IWB) to teach precis and summary writing. The teachers of ESL (English as a Second Language) find it difficult to teach the nuances of these skills, where the students have to compress a long passage into shorter forms. The above are practical skills for work-related situations, where the students need to communicate useful information and leave behind not-so-useful ones. The paper presents a collaborative classroom activity using Interactive Whiteboard (IWB) accompanied by traditional materials to teach the beauty of brevity.